Precarious (Dis)Placement: Temporality and the Legal Rewriting of Refugee Protection in Denmark - Jacobsen, Malene H. (Annals of the American Association of Geographers, 2022)
This article addresses the legal reconfigurations of refuge and its consequences for people displaced by war and state violence. Within Western countries signatory to the 1951 Convention Relating to the Status of Refugees, refugee protection has traditionally served as a solution to conflict-induced displacement by offering a path to permanent residence and citizenship. Yet, in the wake of recent global "refugee crises," several countries have introduced new refugee protection statuses that only allow refugees to stay temporarily. In this article, I focus on one such intervention in Denmark introduced in the fall of 2014, which targets Syrian refugees. Through a feminist geo-legal analysis of this statute and surrounding policy documents, I illustrate how the Danish state has mobilized subtle legal interventions to transform the meaning and character of refugee protection. By differentially classifying groups of refugees according to new calculations of threat and risk, I show how these maneuverings work to deny refugees basic rights and make them subject to intimidation, surveillance, and deportation. I argue that this new statute functions as a legal mechanism of sociospatial b/ordering that produces a series of displacements and limits refugees' access to effective protection under the 1951 Convention. In doing so, I advance critical discussions on temporary protection status, displacement, and refuge.